Light and transmission electron microscopic study on the effect of contraceptive pills on the glomerulus and juxtaglomerular apparatus in mice - Al-Ani, Imad Matloub Dally; Noor Al-Deen, Jinan A.; Kashmola, Muhanad Ali Hamdon (Department of Anatomy, National University of Singapore, 2009)
Light microscopic (LM) and transmission electron microscopic (TEM) observations were performed in the kidneys of oral contraceptive treated mice. Experimental groups were given 0.1 ml of olive oil containing 0.015 fraction of (Neogynon) tablet daily. Control groups were give olive oil alone. Five experimental and three control animals were scarifi ed after 1, 3, 6, 9, and 12 estrus cycles. Glomerulosclerosis, hyaline arteriopathy associated with focal areas of interstitial fi brosis were observed in the fi rst cycle. Mild hypertrophy of juxtaglomerular apparatus “JGA” appeared in the 3rd cycle with increased granularity of the JGCs. Proliferative-sclerosing stages of focal glomerulonephritis were observed and were more advanced in cycle twelve. By transmission electron microscope, there were slight changes in the glomeruli during cycle one. These evident gradually developed in cycle three, thus the glomeruli showed disordered capillary loop occlusion. In cycle six, capillary lumens were occluded by protuberance projection. There were hyperactivity and proliferation of mesangial cells and electron-dense material deposits in glomerular basal lamina; these deposits were accompanied with electron-lucent materials appeared in cycle 9 behind swelled mesangial cells indicating hyperactivity and proliferative cells which showed abundant RER and mitochondria. These lesions were correlated with hyper-granularity of JGCs and hypertrophied JGA. The JGGs appeared in cycle 12 as heterogenized size. These changes indicate that abuse of oral contraceptives is relatively unsafe, especially after long-term of high-dose usage.